2018
DOI: 10.17261/pressacademia.2018.867
|View full text |Cite
|
Sign up to set email alerts
|

A long short term memory application on the Turkish intraday electricity price forecasting

Abstract: Purpose-This paper aims to forecast the Turkish intraday electricity prices accurately. It will be the first intraday electricity price forecasting work, which uses Long-Short Term Memory (LSTM) application. Methodology-LSTM method is based on a special kind of neural network, which is capable of learning long-term dependencies. This paper aims to achieve the best forecasts, in terms of Mean Absolute Error (MAE) and Root Mean Square Error (RMSE), by applying the LSTM model with multistep-ahead prediction appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Similarly, the lagged electricity price, temperature and the economic factors are used to model the hourly electricity demand of Türkiye in another study for the 2013-2015 period using multilayer perceptron, long short-term memory and the gated recurrent unit based models and it is shown that the gated recurrent unit based model gives accurate results (Ugurlu et al, 2018a). Long short-term memory is also used in another work for the estimation of the hourly price of the electricity demand of Türkiye for the period of 2017-2018 and the mean absolute percentage error of 0.24 is achieved (Ugurlu et al, 2018b). Similarly, modelling the hourly electricity demand of Türkiye for the 2012-2014 period is investigated in another study using multilayer perceptron, gradient-descent momentum, Levenberg-Marquardt algorithm and Broyden-Fletcher-Goldfarb-Shanno algorithm and it is concluded that the Broyden-Fletcher-Goldfarb-Shanno algorithm provides accurate results (Gokgoz and Filiz, 2020).…”
Section: Literature Analysismentioning
confidence: 99%
“…Similarly, the lagged electricity price, temperature and the economic factors are used to model the hourly electricity demand of Türkiye in another study for the 2013-2015 period using multilayer perceptron, long short-term memory and the gated recurrent unit based models and it is shown that the gated recurrent unit based model gives accurate results (Ugurlu et al, 2018a). Long short-term memory is also used in another work for the estimation of the hourly price of the electricity demand of Türkiye for the period of 2017-2018 and the mean absolute percentage error of 0.24 is achieved (Ugurlu et al, 2018b). Similarly, modelling the hourly electricity demand of Türkiye for the 2012-2014 period is investigated in another study using multilayer perceptron, gradient-descent momentum, Levenberg-Marquardt algorithm and Broyden-Fletcher-Goldfarb-Shanno algorithm and it is concluded that the Broyden-Fletcher-Goldfarb-Shanno algorithm provides accurate results (Gokgoz and Filiz, 2020).…”
Section: Literature Analysismentioning
confidence: 99%
“…The result of the variable relative importance analysis is presented in descending order in Figure 4. According to the literature, since the impacts of the different lag-orders of the electricity price have a significant impact on the electricity prices, the 1-day (EP_1), 1-week (EP_7), and 2-week (EP_14) lags of the electricity prices were included in the model [50,51]. The most influencing factor affecting electricity prices is renewable electricity in both periods.…”
Section: Variable Importancementioning
confidence: 99%